Innovation in times of crisis: a pragmatic and inclusive approach to cope with urgent global sustainability challenges - Aerni, Philipp (Frontiers in Environmental Economics, 2025)
The term “polycrisis” has become a buzzword to describe the entanglement and reinforcement of multiple global crises that may put the survival of humankind at risk. It builds upon Sustainability Science and its research on the complex interactions of systemic risks. The research approach has its roots in the “Limits to Growth” report published by the Club of Rome in 1972. The publication predicted a global sustainability crisis in response to growing human resource consumption. The threat is real, but there are lessons to be learned from coping with past global crises and how they were addressed by far-sighted government initiatives that incentivized decentralized innovation systems to achieve well-defined objectives. These initiatives proved to be effective because they were based on an adequate understanding of the endogenous nature of economic development and how biocapacity and societal resilience can be enhanced through higher levels of economic complexity. Contemporary European mission-oriented innovation policies (MOIPs) with their strong faith in the state as pacesetter of the economy lack this understanding. In this paper, a more pragmatic innovation policy approach is proposed to accelerate progress on the UN Sustainable Development Goals (UN SDGs) in general, and food security in particular. It combines the target orientation of past US innovation policy missions with the commitment of international crop research networks to mobilize innovation and entrepreneurship for inclusive development. Throughout history, such opportunity-driven approaches proved to be more effective public policy responses to crisis than attempts to minimize systemic risks by limiting growth.